Business longevity and innovation: A Literature Review - Maciej P. KOCZERGA (Communications of International Proceedings, 2023)
This article takes inspiration from various scientific papers advocating for innovation in enterprises, a topic of great significance also in public policies. It has been demonstrated by multiple authors that companies engaging in innovation activities produce superior outcomes compared to those that do not. Most studies and findings in this area are insufficient in providing a thorough examination of the complexities involved in business innovation. It is often implicitely assumed that the primary objective of most enterprises is growth or maximizing short-term profits. It is important to bear in mind that innovative activity results in instability within the company and the implementation of changes, both of which significantly decrease profitability rather than increase it. To comprehensively understand the correlation between enterprise innovation and business longevity determinants across various countries, a thorough literature review was conducted, which included a detailed examination of current research findings. Comparisons in this domain pose a significant challenge. Nonetheless, research on business longevity shows that smaller, often family-owned firms dominate among the oldest enterprises worldwide. It has been found that certain gaps exist in existing studies that have linked innovation to the longevity of enterprises. While some of these studies have openly acknowledged the existence of a positive correlation between innovation and company longevity, it is important to exercise caution when implementing these recommendations. Specifically, it remains unclear how frequently companies should undertake innovative activities, the type of innovations, and the most effective methods for conducting them in a manner that does not undermine or destabilize the company. Despite the unambiguous recommendations of public policies that encourage companies to pursue innovative activities, it is imperative to approach these endeavours with discretion.
Keywords: innovation; business longevity; stability; change